Finite Element Simulation of Acceleration Pedal On XX Vehicle - Nanang Ali Sutisna; Aldhito Hardianto (President University, 2019)
This paper presents the failure analysis of acceleration pedal of xx vehicle. The purpose of this research are to know the cause of failure, types of failure, and approach in searching for the best parameters that yield optimal product quality on product design. This research uses the known test method, where the type of failure and results of analysis compared with the result of expected product reliability. The simulation uses CATIA V5 software involving types of load that applied on product, length, size and dimension of product, and types of material. Simulation result data is used for see the influence and effect of each parameter to the product design, also the types of failure that will affect the product reliability